Chlamydia trachomatis Serovars from the C-Complex and the B- and C-Related Complexes Are Significantly More Pathogenic than Those from the B-Complex in C3H/HeN but Not in BALB/c Mice - Sukumar Pal; Jennifer R. Carmichael; Delia F. Tifrea; Olga Tatarenkova; Luis M. de la Maza (Pathogens)
Studies in humans indicate that certain Chlamydia trachomatis serovars are more pathogenic than others. Specifically, several studies concluded that serovars from the C-complex are more pathogenic than those from the B-complex, although there are reports that do not support this finding. To investigate these results in an animal model, the eight genitourinary C. trachomatis serovars were tested in two strains of mice: C3H/HeN and BALB/c. These two strains of mice were investigated because C3H/HeN is more susceptible to Chlamydia muridarum infections than BALB/c, indicative of differences in their immunogenetic background. Mice were infected transcervically with 105 inclusion forming units of each of the C. trachomatis serovars, and vaginal cultures were collected. To determine the pathogenicity and its impact on fertility, at week seven post-infection, female mice were caged with male mice. In the C3H/HeN mice, significant differences in vaginal shedding and fertility were observed between serovars from the B-complex (D and E) and those from the C-complex (H, I, J) and B- and C-related complexes (G, F, and K). The animals infected with serovars F, G, H, I, J, and K shed less but had significantly more infertility than the mice infected with serovars D or E. The experiments in the BALB/c mice, however, did not show major differences in pathogenicity between the eight C. trachomatis serovars. These results support the findings in humans and emphasize the critical importance of the immunogenetic background of the host on the outcome of C. trachomatis infections. The data imply that management of C. trachomatis-infected patients may require a more personalized approach.